Implementation of Canvas Learning Management System using Google Cloud - Pratama, Fachrizal Rian (Proceeding International Conference on Science and Engineering, 2021)
Abstract. The use of web Learning Management System (LMS) software is often used in schools and universities as online learning. Some of the LMSs that are often used in Indonesia are Moodle, Blackboard CourseSites, Schoology, Latitude Learning, Academy Of Mine, and so on. Apart from the software side, there are also other considerations from the hardware side, because the use of LMS the load on the server becomes very high. The use of cloud computing may be a solution because it is more flexible if you want to increase server capacity. This article will provide how to start using cloud computing and installing Canvas LMS. The superior features, shortcomings, and costs of the LMS are also discussed as reference material when implementing the LMS. Canvas LMS can be used either as online learning in schools or universities, as well as an education-based startup development innovation in Indonesia. Given the importance of educational-based startup applications, examples that exist now are RuangGuru, PesonaEDU, Zenius, Kelase, and so on. One of the paid online applications that already running well is Ruangguru. Ruangguru provides interesting learning material features and is accompanied by interactive learning videos. The added value of developing such LMS-based applications in our own institutions is that it can be adjusted to the curriculum, schedule, and conditions of our own institutions so that this can be an added value and competitiveness of educational applications such as Ruangguru.